18F‐FDG PET/CT for locoregional surveillance following definitive treatment of head and neck cancer: A meta‐analysis of reported studies. Issue 2 (20th November 2018) - Wong, Erin T.; Dmytriw, Adam A.; Yu, Eugene; Waldron, John; Lu, Lin; Fazelzad, Rouhi; de Almeida, John R.; Veit‐Haibach, Patrick; O'Sullivan, Brian; Xu, Wei; Huang, Shao Hui
Abstract: Purpose: To evaluate the performance of 18 F‐fluorodeoxy‐d ‐glucose positron emission tomography‐computed tomography ( 18 F‐FDG PET/CT) in identifying local failure and regional failure following curative radiotherapy or surgery for head and neck squamous cell carcinoma. Methods: A comprehensive literature search identified studies published between January 2010 and August 2016. Diagnostic performance of 18 F‐FDG PET/CT was evaluated for local failure/regional failure stratified by treatment‐to‐scan time interval of ≤3 versus >3 months. Results: Twenty‐four studies (2627 patients) were included. Compared to ≤3 months, 18 F‐FDG PET/CT performed >3 months showed significantly improved sensitivity (87% vs 60%, P = 0.020) and specificity (93% vs 84%, P < 0.001) for local failure. There was no significant difference in sensitivity (79% vs 56%, P = 0.100) or specificity (95% vs 97%, P = 0.35) for regional failure >3 versus ≤3 months. Conclusions: This meta‐analysis confirms high specificity but modest sensitivity of posttreatment 18 F‐FDG PET/CT for local failure and regional failure. Sensitivity and specificity are significantly improved when 18 F‐FDG PET/CT is performed >3 months for local failure.